Penatalaksanaan diare di Rumah pada balita - Arie J. Pitono, Djaswadi Dasuki, Djauhar (Berita Kedokteran Masyarakat (BKM), 2006)
Background: Diarrhoea! diseases are a leading cause of childhood morbidity and mortality in developing countries, and an important cause of malnutrition. Most diarrhoea! deaths are caused by failure to treat acute dehydration properly and to correct electrolyte imbalances. Studies from both the developing and developed world demonstrate that morbidity and mortality can be drastically reduced by the prompt introduction of two simple treatments: oral rehydration therapy and early refeeding. Mother's actions in treating diarrhoea at home, especially in giving oral rehydration and feeding, are very important to reduce morbidity and mortality due to diarrhoea. Methods: This was an observational and cross-sectional study among 245 families with under-five-year-old children with diarrhoea within the last 2 weeks before the survey. The study was based on the longitudinal survey in Purworejo Regency in 2000-2002 by the LPKGM, Gadjah Mada University School of Medicine. Results: Based on the bivariate and multivariate analysis, the variables which related to diarrhoea! duration are the treatment on diarrhoea and the children age. The diarrhoeal treatment showed a very significant relationship with the diarrhoea! duration (p= 0.003). Better diarrhoea! treatment had probability 2.2 times shorter diarrhoeal duration compared with worse diarrhoea! treatment (OR= 2.2; CI 95%= Conclusions: There was a relationship between diarrhoea! treatments at home with the diarrhoea! duration on under-five-year-old children. Better diarrhoeal treatment would have shorter diarrhoeal duration compared with worse diarrhoeal treatment., Another factor influenced the diarrhoea] duration was the children age. Keywords : diarrhoeal treatment. diarrhoeal duration, under-five-year-old children